Integration of individual TiO2 nanotube on the chip: Nanodevice for hydrogen sensing. Issue 3 (25th February 2015) - Enachi, Mihail; Lupan, Oleg; Braniste, Tudor; Sarua, Andrei; Chow, Lee; Mishra, Yogendra K.; Gedamu, Dawit; Adelung, Rainer; Tiginyanu, Ion
Abstract : Titania (TiO2 ) exists in several phases possessing different physical properties. In view of this fact, we report on three types of hydrogen sensors based on individual TiO2 nanotubes (NTs) with three different structures consisting of amorphous, anatase or anatase/rutile mixed phases. Different phases of the NTs were produced by controlling the temperature of post‐anodization thermal treatment. Integration of individual TiO2 nanotubes on the chip was performed by employing metal deposition function in the focused ion beam (FIB/SEM) instrument. Gas response was studied for devices made from an as‐grown individual nanotube with an amorphous structure, as well as from thermally annealed individual nanotubes exhibiting anatase crystalline phase or anatase/rutile heterogeneous structure. Based on electrical measurements using two Pt complex contacts deposited on a single TiO2 nanotube, we show that an individual NT with an anatase/rutile crystal structure annealed at 650 °C has a higher gas response to hydrogen at room temperature than samples annealed at 450 °C and as‐grown. The obtained results demonstrate that the structural properties of the TiO2 NTs make them a viable new gas sensing nanomaterial at room temperature. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : In this Letter, the authors report on three types of hydrogen sensors based on individual TiO2 nanotubes (NTs) with three different structures consisting of amorphous, anatase or anatase/rutile mixed phases. The response for the sensor based on mixed anatase/rutile crystal structures is the highest one. The obtained results demonstrate that the structural properties of the TiO2 NTs make them a viable new gas sensing nanomaterial at room temperature.